Youth engagement the civic-political lives of children and youth - Nenga, Sandi Kawecka; Taft, Jessica K. (Bingley, U.K. : Emerald, 2013)
In recent years, civic and political institutions have stepped up their efforts to encourage youth participation: schools promote volunteerism, non-profits provide opportunities for service, local governments create youth councils, and social movement organizations discuss the need to encourage a new generation of activists. This volume adopts a critical approach to the civic and political socialization projects which aim to transform children and youth into upstanding citizens. By synthesizing the study of young peoples civic and political socialization under the rubric of "Youth Engagement", the interplay of the civic and the political throughout young peoples lives is considered. Chapters critically examine the multiple and contested meanings of ideal citizenship and reveal how children and youth craft active citizenship as they encounter and respond to the various institutions and organizations designed to encourage their civic and political development.
Introduction : conceptualizing youth engagement / Sandi Kawecka Nenga, Jessica K. Taft -- A different girl effect : producing political girlhoods in the 'invest in girls' climate / Emily Bent -- Rethinking children's participation in democratic processes : a right to play / Stuart Lester -- Educating active citizens : what roles are students expected to play in public life? / L. Alison Molina-Girón -- Engaging young people? : the experiences, challenges, and successes of Canadian youth advisory councils / Christopher D. O'Connor -- Bridging worlds in the social studies classroom : teachers' practices and Latino immigrant youths' civic and political development / Rebecca M. Callahan, Kathryn M. Obenchain -- 'They have their hands on the pulse of the city' : teachers' constructions of students' civic knowledge in an urban middle school classroom / Shira Eve Epstein -- Civic engagement and the emergence of race : American youth negotiate citizenship / Shauna A. Morimoto -- Mexican immigrant children and youth's contributions to a community centro : exploring civic engagement and citizen constructions. / Jocelyn Solís, Jesica Siham Fernández, Lucia Alcalá -- 'My mother and father are African, but I'm Norwegian' : immigrant children's participation in civic society in Norway / William A. Corsaro, Berit O. Johannesen, Lily Appoh -- Learning from each other : collective practices in making independent youth media / Rachel Kulick.
Print version record
Keywords: Social Science -- Children's Studies; Social Science -- Sociology -- General; Social issues (Children's/YA); Age groups: adolescents; Children and politics; Children -- Social conditions; Children's rights; Globalization